2006
DOI: 10.1086/508068
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Gene Encoding the Enzyme Deficient in Mucopolysaccharidosis IIIC (Sanfilippo Disease Type C)

Abstract: Mucopolysaccharidosis IIIC (MPS IIIC), or Sanfilippo C, represents the only MPS disorder in which the responsible gene has not been identified; however, the gene has been localized to the pericentromeric region of chromosome 8. In an ongoing proteomics study of mouse lysosomal membrane proteins, we identified an unknown protein whose human homolog, TMEM76, was encoded by a gene that maps to 8p11.1. A full-length mouse expressed sequence tag was expressed in human MPS IIIC fibroblasts, and its protein product l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
99
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(103 citation statements)
references
References 14 publications
4
99
0
Order By: Relevance
“…Eight insertions and deletions affecting exons 5, 7, 11, 13, 17, and 18 of the HGSNAT gene (Table 1) have been already reported. In particular: mutations c.1034_1049del, c.1336_1372dup, and c.1750delG in patients from the Czech Republic, Poland, and Finland, respectively, were reported in our original publication, whereas Fedele et al [2007] reported mutations c.682_740del, c.739delA, and c.1669_1674delinsACAT, present in patients of Italian origin, and Fan et al [2006] found c.1345dupG in a Canadian patient. Interestingly, the single base deletion, c.739delA, predicted to result in a frameshift and the appearance of a premature termination codon (PTC) 87 bp downstream from the deletion, was also found in homozygous fashion in a patient from North Africa and in combination with p.R506X in a Belgian patient.…”
Section: Insertions and Deletionsmentioning
confidence: 71%
See 3 more Smart Citations
“…Eight insertions and deletions affecting exons 5, 7, 11, 13, 17, and 18 of the HGSNAT gene (Table 1) have been already reported. In particular: mutations c.1034_1049del, c.1336_1372dup, and c.1750delG in patients from the Czech Republic, Poland, and Finland, respectively, were reported in our original publication, whereas Fedele et al [2007] reported mutations c.682_740del, c.739delA, and c.1669_1674delinsACAT, present in patients of Italian origin, and Fan et al [2006] found c.1345dupG in a Canadian patient. Interestingly, the single base deletion, c.739delA, predicted to result in a frameshift and the appearance of a premature termination codon (PTC) 87 bp downstream from the deletion, was also found in homozygous fashion in a patient from North Africa and in combination with p.R506X in a Belgian patient.…”
Section: Insertions and Deletionsmentioning
confidence: 71%
“…Below we summarize all previously identified mutations and present them with a unified numbering system based on the sequence of GenBank entries NM_152419.2 and NG_009552.1 as previously reported [Fan et al, 2006;Ruijter et al, 2008;Fedele et al, 2007]. We also report 10 novel mutations, including those identified in patient families from Pakistan, the United States, the UK, Germany, Greece, Turkey, and Belarus.…”
Section: Mutations and Their Biological Relevancementioning
confidence: 90%
See 2 more Smart Citations
“…Over time, airway obstruction and/or pulmonary infection can lead to cardiopulmonary arrest. A subtype, Sanfilippo type C syndrome is caused by deficiency of alpha-glucosamine N-acetyltransferase encoded by HGSNAT [4]. No disease-modifying treatment is presently available.…”
mentioning
confidence: 99%